Comparative Evaluation of Tear Film and Corneal Surface in Chronic Smokers and Non Smokers: A Cross-sectional Study - Ruchi Dabas; Meena Kumari; Manisha Rathi; Monika Dahiya; Rajni Yadav; Sumit Sachdeva (Journal of Clinical and Diagnostic Research)
Introduction: Tobacco smoking is the primary avoidable cause of mortality, resulting in the deaths of seven million people worldwide annually. Tobacco smoke is a well-documented ocular irritant that exacerbates Dry Eye Disease (DED) and its associated symptoms. Aim: To compare tear film and corneal surface parameters in chronic smokers and non smokers. Materials and Methods: This cross-sectional study was conducted among chronic smokers and non smokers presenting at a tertiary eye care centre in Northern India. A total of 80 subjects were included in the study and divided into two groups of 40 subjects each, comprising group A (chronic smokers) and group B (non smokers). All participants underwent a series of measurements: Schirmer I test, Tear Breakup Time (TBUT), Central Corneal Thickness (CCT) and endothelial cell count using specular microscopy. Results: The mean age of smokers was 50.15±6.89 years, whereas the mean age of non smokers was 49.25±6.39 years, with a significant male preponderance. The dry eye parameters, such as the Schirmer I test and TBUT, were significantly lower in smokers compared to non smokers, with a statistically significant difference (p-value <0.001). Similarly, CCT and endothelial cell count were significantly lower in smokers than in non smokers, with a statistically significant difference (p-value <0.001). Conclusion: The study highlights the detrimental effects of smoking on ocular surface health. Smoking predisposes users to DED due to lower tear production and an unstable tear film.